Resolution of Uterine Torsion with Incomplete Cervical Dilation through Caesarean Section in a Crossbred Cow - Vasantbhai Patel, Anshu; Maheshkumar Kapadiya, Falgun; Bhavarsinh Solanki, Gajendrasinh; Jitubhai Chavda, Karansinh; Naranbhai Suthar, Dipak (The Indian Journal of Animal Reproduction, 2025)
A four years old crossbred cow was presented to the Veterinary Clinical Complex (VCC), with a history of full-term preg nancy and signs of labour in the past 15 hours. The case was confirmed left side uterine torsion through per rectal and vaginal examination. Left side uterine torsion was relieved with modified Schaffer’s method but cervical dilatation was not established, inspite of appropriate treatment. The left flank para median site was prepared for performing Caesarean section. The surgical site was prepared aseptically with povidone-iodine solution and anesthetized by local infiltration with 2% lignocaine. A dead emphysematous male calf around 39 kg was delivered from the incision site. The uterine wall was closed with continuous cushing suture pattern, followed by continuous Lembert suture pattern. The animal was treated with standard treatment protocol and skin sutures were removed at 15 days after surgery.